2017
DOI: 10.1182/blood-2017-03-742346
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DP in unrelated hematopoietic cell transplantation revisited: challenges and opportunities

Abstract: When considering HLA-matched hematopoietic cell transplantation (HCT), sibling and unrelated donors (UDs) are biologically different because UD-HCT is typically performed across HLA-DP disparities absent in sibling HCT. Mismatched HLA-DP is targeted by direct alloreactive T cell responses with important implications for graft-versus-host disease and graft-versus-leukemia. This concise review details special features of HLA-DP as model antigens for clinically permissive mismatches mediating limited T-cell allor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 79 publications
2
50
1
1
Order By: Relevance
“…Previous studies have shown that rejected graft-specific CD4 + and CD8 + T cells derived from the "winner" UCB can recognize leukemic cells in dUCBT studies [7,8,12,23]. In addition, mismatch of HLA-DPB1 between the "winner" UCB and the recipient likely would reduce the risk of relapse in different patterns of HSCT [22,31,32]. The mechanism and effector cell population(s) remain unclear, however, requiring further laboratory research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that rejected graft-specific CD4 + and CD8 + T cells derived from the "winner" UCB can recognize leukemic cells in dUCBT studies [7,8,12,23]. In addition, mismatch of HLA-DPB1 between the "winner" UCB and the recipient likely would reduce the risk of relapse in different patterns of HSCT [22,31,32]. The mechanism and effector cell population(s) remain unclear, however, requiring further laboratory research.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations. First, we only analyzed HLA‐A, ‐B, ‐C, and DRB1 loci and did not examine other class II HLA loci such as HLA‐DPB1 and HLA‐DQB1, although they have also been suggested to influence transplantation outcomes in recent studies . Second, some patient populations were too small for a detailed analysis, such as a precise calculation of the distribution or combinations of mismatched HLA loci in each pair.…”
Section: Discussionmentioning
confidence: 99%
“…There are several encouraging new ways to prevent and to treat GVHD including modification of the gut microbiome [30,49,82]; it is now time to select donors according to their immune repertoire and their genetic background for T cell activation. Possibly this can be combined with an anti-leukemic effect based on anti-microbial activity [50,62] and HLA class II DP histocompatibility [83]. The immune repertoire may be primed by prior infections as they may be primed by prior transfusions and pregnancies, but activation may be decisive that is induced by the actual microbiome and determined genetically by the donor and the host.…”
Section: Discussionmentioning
confidence: 99%